Comprehensive N‐glycosylation analysis of the influenza A virus proteins HA and NA from adherent and suspension MDCK cells. (15th March 2021) - Pralow, Alexander; Hoffmann, Marcus; Nguyen‐Khuong, Terry; Pioch, Markus; Hennig, René; Genzel, Yvonne; Rapp, Erdmann; Reichl, Udo
Abstract : Glycosylation is considered as a critical quality attribute for the production of recombinant biopharmaceuticals such as hormones, blood clotting factors, or monoclonal antibodies. In contrast, glycan patterns of immunogenic viral proteins, which differ significantly between the various expression systems, are hardly analyzed yet. The influenza A virus (IAV) proteins hemagglutinin (HA) and neuraminidase (NA) have multiple N ‐glycosylation sites, and alteration of N ‐glycan micro‐ and macroheterogeneity can have strong effects on virulence and immunogenicity. Here, we present a versatile and powerful glycoanalytical workflow that enables a comprehensive N ‐glycosylation analysis of IAV glycoproteins. We challenged our workflow with IAV (A/PR/8/34 H1N1) propagated in two closely related Madin–Darby canine kidney (MDCK) cell lines, namely an adherent MDCK cell line and its corresponding suspension cell line. As expected, N ‐glycan patterns of HA and NA from virus particles produced in both MDCK cell lines were similar. Detailed analysis of the HA N ‐glycan microheterogeneity showed an increasing variability and a higher complexity for N ‐glycosylation sites located closer to the head region of the molecule. In contrast, NA was found to be exclusively N ‐glycosylated at site N73. Almost all N‐ glycan structures were fucosylated. Furthermore, HA and NA N ‐glycan structures were exclusively hybrid‐ and complex‐type structures, to some extent terminated with alpha‐linked galactose(s) but also with blood group H type 2 and blood group A epitopes. In contrast to the similarity of the overall glycan pattern, differences in the relative abundance of individual structures were identified. This concerned, in particular, oligomannose‐type, alpha‐linked galactose, and multiantennary complex‐type N ‐glycans. Abstract : The influenza A virus (IAV) proteins hemagglutinin and neuraminidase display multiple N ‐glycosylation sites. Alteration of N ‐glycan micro‐ and macroheterogeneity can have strong effects on virulence and immunogenicity. We present a versatile and powerful glycoanalytical workflow that enables comprehensive site‐specific and fine‐structural N ‐glycan analysis of IAV glycoproteins and investigate the glycosylation of IAV propagated in two closely related Madin‐Darby Canine Kidney cell lines (suspension and adherent).